PUASE DIAGRAM OF KONDO NECKLACIMODEL TO FINITE TEMPERATURE - Reyes, D. (2005)
A simplified version of the Kondo lattice model, thc Kondo necklace model, is studied at finite temperature using a representation for the localized and conduction electron spins in terms of local Kondo singlet and triplet operators. We calculate the double time Green's functions to get the dispersion relation of the excitations of the system. We show that in 3-d there is an antiferromagnetic ordered state at finite temperatures, but in 2-d long range magnetic order occurs only at T O.